A Call for Heresy : Why Dissent Is Vital to Islam and America - Majid, Anouar, 1960- (Book collections on Project MUSE., 2007)
A Call for Heresy discovers unexpected common ground in the deepening conflict between the Islamic world and the United States. Anouar Majid argues that the Islamic world and the United States are both in precipitous states of decline because, in each, religious, political, and economic orthodoxies have silenced the voices of their most creative thinkers. The solution, Majid argues, is a long-overdue revival of dissent.